Performance of the General Directorate of Civil Defense during the Hajj season in terms of emergency management - Ahmad Saad, Al-Ahmadi; Abas, Zakaria; Abdul Ghani, Abdullah (Universiti Sains Malaysia, 2010)
Hajj is the greatest assembly of humankind on earth. More than 2.3 million Muslims attended Hajj this year. During the Hajj period, the mass gathering and movement of pilgrims can at times lead to injury, death, and damage to property and the environment. The increasing number of pilgrims along with their diverse origin and characteristics contributes to the challenging task of minimizing emergencies and risk during the Hajj. The purpose of this research is to examine how the integration of complex environments (Hajj Environment) can improve the General Directorate for Civil Defense (GDCD) task performance in emergency operations. This study will highlight the major factors that assist and impede in performing the work and services of GDCD for encountering the crises and disasters in their various stages during the hajj season and, maintain the safety of pilgrims and their property.